(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article examines the Ukrainian motifs in the prose works of R.M. Rilke “Song of Truth”, “How old Timothy died singing”, written after traveling to Ukraine in the early twentieth century. It is stated that Ukrainian culture, Christian traditions, Ukrainian songs about the Cossacks had a great influence on the spirituality of the artist. The history of Ukraine in the prose of R.M. Rilke is read through the mentions of the glorious Cossack leaders – Ostryanytsya, Nalyvayka, Bulba – fighters for national and social liberation. The main attention is paid to the depiction in the works of images of folk singers – kobzars Ostap, Tymofiy Ivanovych and their creative heritage. The creative interpretation of the images of kobzars brings together the prose of R.M Rilke with the works of T. Shevchenko, Natalia Korolyova, and the Ukrainian folklore tradition. The topos of Rus’ is nominally represented by the “holy city” of Kyiv and a typical Ukrainian village. As a result of the analysis, the role of the song, the icon in the peasant cultural space is determined. In his works, the Ukrainian world is determined by the patriarchal-Christian way of life, subordinated to the cyclical natural process of life. It is stated that the reflection of the folk religious consciousness in the works are domestic icons. Emphasis is placed on the sacredness of the living space and the sacred significance of icons in the homes of Ukrainians for the heroes of “Songs of Truth”. The story “How old Timothy died singing” points to the role of song in the life of the people, its life-giving power, which a talented performer must pass on to children. Immersion in the folk song element, in the Ukrainian world, the use of folklore images in the works allowed the author to recreate the spiritual and cultural heritage of Ukrainians.